Zakat Infaq and Sadaqah as a Modern Fiscal Instrument in Indonesia - Hilmi, Ahmad; Janwari, Yadi; Al-Hakim, Sofyan (MUAMALATUNA, 2023)
This study investigates the integration of Zakat, Infaq, and Sadaqah (ZIS) in Indonesia's modern fiscal policy framework. The research method involves analysing the impact of ZIS on economic growth, wealth distribution, and social inclusion. The background problem arises because although ZIS has been proven to contribute positively to the welfare of society, its integration as a critical component of fiscal policy is still limited. Challenges involve regulatory formulation, efficient fund management, public awareness, and harmonisation of sharia objectives. This research is expected to provide recommendations to policymakers to design effective strategies for integrating ZIS in fiscal policy, with positive impacts on Indonesia's economic efficiency, social cohesion, and economic justice.